2011
DOI: 10.1007/s00420-011-0676-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genotoxic and oxidative effects in workers exposed to jet propulsion fuel

Abstract: Urinary 1-and 2-naphthol levels of exposed workers were found to be significantly higher than those of control subjects. Occupational exposure to JP-8 resulted in no significant genotoxic and oxidative effects, while smoking is the principal confounding factor for the some parameters. To understand the genotoxic and oxidative effects of JP-8 exposure, further studies should be planned to find out whether human populations may be at increased risk for cancer because of the exposures related to occupation and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…An Italian study reported DNA aberrations in airport staff (sister chromatid exchange and total structural chromosomal changes in lymphocytes and exfoliated buccal cells) with increased tail moment in the comet assay compared to unexposed controls [6]. Evaluation of airport workers in Turkey [7] and at an American aircraft equipment military station [8] also showed a significant increase in the frequency of sister chromatid exchange in the exposed workers. Recently, it was shown that 2 hours of normal breathing in a high-concentration airport-particle zone downwind of Los Angeles airport increased the acute systemic inflammatory cytokine IL-6 of non-smoking adults with asthma [9].…”
Section: Introductionmentioning
confidence: 99%
“…An Italian study reported DNA aberrations in airport staff (sister chromatid exchange and total structural chromosomal changes in lymphocytes and exfoliated buccal cells) with increased tail moment in the comet assay compared to unexposed controls [6]. Evaluation of airport workers in Turkey [7] and at an American aircraft equipment military station [8] also showed a significant increase in the frequency of sister chromatid exchange in the exposed workers. Recently, it was shown that 2 hours of normal breathing in a high-concentration airport-particle zone downwind of Los Angeles airport increased the acute systemic inflammatory cytokine IL-6 of non-smoking adults with asthma [9].…”
Section: Introductionmentioning
confidence: 99%
“…Lemasters et al 37 assessed genotoxic changes in aircraft maintenance personnel exposed to solvents and jet fuel (mostly JP-4) in a sequential study, and reported a small but statistically significant increase in the frequency of SCE of a group of workers after 30 weeks of exposure, while observing a non-statistically significant increase in micronuclei frequency in the unexposed group. SCE frequency was also observed to be higher in the exposed group of military air force workers in a cross-sectional study from Erden et al accompanied by a no difference in micronuclei frequency 22 . Pitarque et al did not detect changes in SCE in a cross-sectional study among airport workers, but observed lower micronuclei frequency in the exposed group, and small increase in DNA damage detected by the comet assay 38 .…”
Section: Discussionmentioning
confidence: 82%
“…However, a field study among firefighters did not indicate genotoxicity in PBMCs after a work shift, which was considered to be related to both low exposure during the work shift under study and possibly carry-over from previous exposures, even though the firefighters were monitored after three days off 36 . Previous studies on jet fuel exposure among aircraft and airport workers assessed genetic damage by sister chromatic exchange (SCE), micronuclei frequency, chromosomal aberrations, DNA strand breaks and oxidatively damaged DNA with inconsistent results 22 , 37 40 . Lemasters et al 37 assessed genotoxic changes in aircraft maintenance personnel exposed to solvents and jet fuel (mostly JP-4) in a sequential study, and reported a small but statistically significant increase in the frequency of SCE of a group of workers after 30 weeks of exposure, while observing a non-statistically significant increase in micronuclei frequency in the unexposed group.…”
Section: Discussionmentioning
confidence: 99%